Illness and injuries in athletes with visual impairment at the London 2012 Paralympic Games - Stopforth, Louise (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Background: Participation in sport by athletes with impairment has grown and evolved rapidly since the inception of the Paralympic Games. Athletes with visual impairment were first included in the Paralympic Games in 1976. Surveillance of illnesses and injuries forms the first important step in determination of the epidemiology and an understanding of the risk factors for both illness and injuries in these populations. Thus, surveillance can therefore assist medical teams in implementing prevention strategies. Few studies have evaluated the incidence of illness and injuries amongst athletes with impairment. For this reason, a novel web based injury and illness surveillance system (WEBIISS) was developed for use by the team physicians at the London 2012 Paralympic Games. To our knowledge, no study has specifically researched the epidemiology of illness and injuries in athletes with visual impairment during a major sport event such as the Paralympic Games. Objective: To determine the incidence associated with illness and injuries in athletes with visual impairment during the London 2012 Paralympic Games. We further aim to describe any differences between sports, age groups, gender and body systems affected in this cohort of athletes. Methods: This study was a retrospective analysis of a component of the large prospective cohort study on the epidemiology of injury and illness conducted over a 14-day period at the London 2012 Paralympic Games. The data from 711 of the 791 athletes with visual impairment who participated in the London 2012 Paralympic Games were analyzed. The following data sources were used: Firstly, de-identified information regarding age, gender, impairment, country code and sports code of athletes obtained from the International Paralympic Committee database. Secondly, information collected from the electronic medical data capture system (EMDCS) used at all the London Organizing Committee for the Olympic and Paralympic Games (LOCOG) medical stations; and thirdly a novel web-based injury and illness surveillance system (WEB-IISS) used by the team physicians. This is the most comprehensive reporting system used in elite athletes with impairment to date. Data were collected on a daily basis from 3 days prior to the start of the Paralympic Games (pre-competition period) until the last day of the 11-day Paralympic Games (competition period). Definitions: In order to determine the nature and extent of illnesses and injuries as well to enable uniformity in research studies evaluating the data collected during the London 2012 Paralympic Games, the following definitions were implemented: Illness was defined as 'any newly acquired illness as well as exacerbation of pre-existing illness that occurred during training or competition, and during or immediately before the London 2012 Paralympic Games'. Injury was defined as 'any newly acquired injury as well as exacerbation of pre-existing injury that occurred during training and/or competition period of the London 2012 Paralympic Games'. Incidence rate (IR) of illness or injury is the number of illnesses or injuries per 1000 athlete days. Incidence proportion (IP) of illness or injury is the proportion of athletes affected by illness or injury (n/100). Results: Incidence rate of illness (IR 11.9; 95% CI 9.0 - 15.7) was similar to incidence rate of injuries (IR 14.5; 95% CI 11.3 - 18.5) in VI athletes. The IR of illness for VI athletes (IR 11.9; 95% CI 9.0 - 15.7) compared well to that of illness for all impairment groups (IR 12.7; 95% CI 10.2 - 16.0). Furthermore, the IR of injuries for VI athletes (IR 14.5; 95% CI 11.3 -18.5) compared well to that of injuries for al impairment groups (IR 12.6; 95% CI 10.3 - 15.4). Gender and age did not affect the risk of illness or injuries in VI athletes. Furthermore, there was a higher IR of illness for swimmers with visual impairment compared to other sports, but this was not statistically significant. The IR of illness for VI athletes participating in swimming was 12.5 (95% CI 8.8 - 17.8) compared to that of VI non-swimmers, IR 11.8 (95% CI 8.9 - 15.6). Participation in athletics (track and field) was associated with a slightly higher risk for injury for athletes with VI compared to other sports, but this was not statistically significant. The IR of injury was 15.8 (95% CI 11.6 - 21.5) and the IP 22.1 (95% CI 16.3 - 30.1) for VI track and field athletes. The IR of injury was 13.0 (95% CI 9.6 - 17.4) and IP 18.1 (95% CI 13.5 - 24.3) amongst VI athletes not participating in track and field athletics. VI swimmers had a lower IR of injury (IR 4.1; 95% CI 1.8 - 9.5) than VI non-swimmers (IR 16.1; 95% CI 12.6 - 20.7) (p=0.002). There was a higher IR and IP of lower limb injuries compared to upper limb injuries in athletes with visual impairment. The IR for lower limb injuries in athletes with visual impairment was 7.7 (95% CI 5.8 - 10.3) and the IP was 10.8 (95% CI 8.1 - 14.4). The average IR of lower limb injuries for all para-athletes was 4.5 (95% CI 3.5 - 5.7). The IR for upper limb injuries in athletes with visual impairment was 3.0 (95% CI 1.9 - 4.5) and the IP was 4.1 (95% CI 2.7 - 6.3). The average IR for upper limb injuries for all para-athletes was 4.5 (95% CI 3.5 - 5.9). Conclusion: The findings of this study suggest that Paralympic athletes with VI had a similar incidence rate of illness and injury compared to other impairment groups; and IR of illness was similar to that of injuries. Risk of illness or injury was not affected by age group or gender, but rather sport specific differences were observed. Of particular interest was the fact that athletes with VI had a higher incidence rate of lower limb injuries than upper limb injuries.